Advances in design, simulation and manufacturing IV Proceedings of the 4th international conference on Design, Simulation, Manufacturing: The Innovation Exchange, DSMIE-2021, June 8–11, 2021, Lviv, Ukraine - Volume 2: Mechanical and Chemical Engineering - Ivanov, Vitalii; Pavlenko, Ivan; Liaposhchenko, Oleksandr; Machado, José; Edl, Milan (Switzerland Springer, 2021)
This book reports on topics at the interface between mechanical and chemical engineering, emphasizing design, simulation, and manufacturing. Specifically, it covers recent developments in the mechanics of solids and structures, numerical simulation of coupled problems, including fatigue, fluid behavior, particle movement, pressure distribution. Further, it reports on developments in chemical process technology, heat and mass transfer, energy-efficient technologies, and industrial ecology. Based on the 4th International Conference on Design, Simulation, Manufacturing: The Innovation Exchange (DSMIE-2021), held on June 8-11, 2021, in Lviv, Ukraine, this second volume of a 2-volume set provides academics and professionals with extensive information on trends, technologies, challenges and practice-oriented experience in the above-mentioned areas.
Electronic reproduction
Keywords: Mechanics, Applied; Solids; Production engineering; Materials; Thermodynamics; Heat engineering; Heat -- Transmission; Mass transfer; Electronic books